An Update on Less Invasive and Endoscopic Techniques Mimicking the Effect of Bariatric Surgery - Froukje J. Verdam; Ruben Schouten; Jan Willem Greve; Ger H. Koek; Nicole D. Bouvy (Journal of Obesity)
Obesity (BMI 30–35 kg/m2) and its associated disorders such as type 2 diabetes, nonalcoholic fatty liver disease, and cardiovascular disease have reached pandemic proportions worldwide. For the morbidly obese population (BMI 35–50 kg/m2), bariatric surgery has proven to be the most effective treatment to achieve significant and sustained weight loss, with concomitant positive effects on the metabolic syndrome. However, only a minor percentage of eligible candidates are treated by means of bariatric surgery. In addition, the expanding obesity epidemic consists mostly of relatively less obese patients who are not (yet) eligible for bariatric surgery. Hence, less invasive techniques and devices are rapidly being developed. These novel entities mimic several aspects of bariatric surgery either by gastric restriction (gastric balloons, gastric plication), by influencing gastric function (gastric botulinum injections, gastric pacing, and vagal nerve stimulation), or by partial exclusion of the small intestine (duodenal-jejunal sleeve). In the last decade, several novel less invasive techniques have been introduced and some have been abandoned again. The aim of this paper is to discuss the safety, efficacy, complications, reversibility, and long-term results of these latest developments in the treatment of obesity.